The Knowledge Production Unity like a answer to the methodological challenges of the 21th century's education - Judith LEÓN GUEVARA (Ediciones Universidad de Salamanca, 2011)
The Knowledge Production Unity methodology develop a model to abord the knowledge, and propose a didactic by whose steps are necessary to reach a ownlearning process and a guide construction of knowledge, for a significative effect in the university.